Mathematical modeling and analysis of elastic waves in a thermo piezoelectric multilayered rotating composite rod with LEMV/CFRP interface - Selvamani, R.; Mahesh, S. (Technische Mechanik - European Journal of Engineering Mechanics, 2020)
In this present paper, we form the mathematical model for wave propagation in a thermo piezoelectric multilayered rotating composite rod made of inner and outer piezoelectric layer bonded together by Linear Elastic Materials with voids (LEMV).To uncouple the equation of motion, electric and heat conduction equations, displacement potential functions are introduced. The frequency equations are obtained for longitudinal and flexural modes of vibration and are studied numerically for heat conducting PZT-5A material.The computed non-dimensional frequency is presented in the form of dispersion curves against various physical quantities. Adhesive layer Linear Elastic Materials with Voids (LEMV) is compared with Carbon Fibre Reinforced Polymer (CFRP).We found that the frequency wave characteristics are more stable and realistic in the presence of thermal, electrical and the rotation parameters.